MENGANALISIS FUNGSI IMPLISIT PADA KECEPATAN DAN PERCEPATAN MOBIL-MOBILAN PADA MASSA YANG BERBEDA - Riris Purbosari; Imas Ratna Ermawaty (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
This study aims to observe, calculate and assess the implicit function in experimental velocity and acceleration of cars with different masses. Based on the hypothesis of the influence of different mass to the speed and acceleration of cars by using the implicit function, no difference in the distance followed. The method used in the study is the experimental method. With the population is the speed and the sampling is different mass and constant load. The constant load is placed on the disk load that then linked directly to the rope (the rope length is l) and connected to the toy car. Cars placed according to the distance of 80 cm and 100 cm (which is already measured), noted latency. Concluded that the different masses affect the velocity and acceleration using implicit function analysis. The faster moving cars the less time it took the toy car. As well as great speed and acceleration experienced by the different cars each of its mass. The greater the mass of owned cars, the lesser speed of these cars. Applies to acceleration, where the greater mass will be smaller acceleration obtained. The smaller the mass, the greater the acceleration is obtained.Keywords: distance, velocity, acceleration, mass and function implicitly.